Comparative Technical Review of IS 456:2000 and IS 456 (Draft-5): Design Philosophy, Durability Governance and Professional Impact (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The proposed evolution of IS 456 into IS 456 (Draft-5) marks a decisive recalibration of structural concrete philosophy in India. Whereas IS 456:2000 was predominantly strength-oriented within a prescriptive limit-state framework, Draft-5 advances a performance-governed doctrine integrating strength, serviceability control, durability verification, and lifecycle accountability.This study presents a structured comparative technical review of the two frameworks, examining scope integration, serviceability elevation, exposure-driven durability reasoning, and documentation governance. The analysis indicates a clear migration from tabulated compliance toward engineered performance justification, with measurable implications for detailing density, material specification, and professional workflow.Draft-5 therefore represents not a routine revision, but a governance transition—shifting Indian structural design from strength sufficiency to accountable, service-life–oriented performance.